Dual-curable stereolithography resins for superior thermomechanical properties - O. Konuray; F. Di Donato; M. Sangermano; J. Bonada; A. Tercjak; X. Fernandez-Francos; A. Serra; X. Ramis (eXPRESS Polymer Letters)
Stereolithography (SL) stands out as a relatively fast additive manufacturing method to produce thermoset components with high resolutions. The majority of SL resins consist of acrylate monomers which result in materials with curing-induced shrinkage problems and this, in addition to the incomplete and non-uniform conversions reached in the SL process, results in poor mechanical properties. To address this issue, a dual-curing formulation was developed by mixing an epoxy monomer into a commercial multi-acrylate SL resin: the first curing stage is acrylate free-radical photopolymerization at ambient temperature, and the second curing stage is cationic epoxy homopolymerization at higher temperatures. The fully dual-cured materials are macroscopically homogeneous, with nanoscale domains observed by Atomic Force Microscopy (AFM), and with unimodal tan delta peaks observed in Dynamic Mechanical Analysis (DMA). The uncured material was storage stable at ambient conditions for at least 9 weeks since the epoxy part was virtually unreactive at these temperatures. With the dual-cured materials, a nearly 10-fold increase in Young’s modulus was achieved over the neat acrylate resin. At the thermal curing stage, the presence of diperoxyketal thermal radical initiator to the liquid formulation facilitated the polymerization of unreacted acrylates that remained from the SL process simultaneously with epoxy homopolymerization and helped the material attain improved properties.